Enhancing Student Engagement in Online Learning through a Peer-to-Peer Virtual Reality Application - Abdulrazak, Saleh; Winchell Alexis, Chong Yeng Yong; Mohd Kamal, Othman; Mohamad Hardyman, Barawi; Shaziti, Aman (Oslo Metropolitan University, 2025)
This study addresses the challenges of reduced student engagement in online learning, exacerbated by the COVID-19 pandemic. It explores the potential of a peer-to-peer learning application using virtual reality (VR) components to enhance student engagement in a Python programming course. The application was developed and tested with university students, focusing on usability, social presence, and learning performance. Usability testing revealed positive perceptions of the virtual classroom's realism, with a mean score of 36.47 out of 45 for realism. Participants also positively viewed the possibility to act and examine the virtual environment. There were concerns about the interface quality, with a mean score of 9.13 out of 15. Self-evaluation of performance was high, with a mean score of 10.33 out of 15. Sound quality was generally perceived positively, with a mean score of 16.07 out of 20. Learning performance showed significant improvement in both traditional (pre-test mean = 8.53, post-test mean = 12.07) and proposed VR learning groups (pre-test mean = 10.03, post-test mean = 15.50). The proposed VR learning method demonstrated a greater increase in knowledge (mean improvement = 5.47) compared to the traditional method (mean improvement = 3.53). Results indicated significant knowledge improvement and positive user feedback, suggesting that VR-based peer-to-peer learning can be a promising approach to improve student engagement in online settings.